Simplified Concrete Resistivity and Rapid Chloride Permeability Test Method - Riding, Kyle A.; Poole, Jonathan L.; Schindler, Anton K.; Juenger, Maria C. G.; Folliard, Kevin J. (My University, 2010)
A simplified method of measuring concrete resistivity, as an index of permeability, has been developed that is similar to ASTM C1202 or the rapid chloride permeability test (RCPT). It is significantly faster and easier to perform, however. In this test, cylinders 100 x 200 mm (4 x 8 in.) were cured in 100% relative humidity and tested using the same solutions, test cells, and rubber gaskets as specified in ASTM C1202. To eliminate the problem of the temperature rise of the sample during the test, only one current reading was taken (after 5 minutes) that could be used to calculate the concrete resistivity. Testing was conducted on various different concrete mixtures after 91 days of moist curing using both the new quicker method and the standard ASTM C1202 method. An empirical correlation between the new method and the standard method demonstrates the validity and promise of the new method.
Keywords: Concrete permeability; Rapid chloride permeability test; Resistivity